KASHMIR; SENGKETA PERBATASAN INDIA-PAKISTAN DAN ANALISIS HUKUM INTERNASIONAL - Khaeruddin Khaeruddin; Nur Afdalia (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
Kashmir is a region in South Asian located at the foot of the Himalayas and is nicknamed as paradise.  This makes the Kashmir region a target of the surrounding countries, thus becoming a very disturbing conflict in the South Asian region.  The research method used in this study is a qualitative method and a literature study that aims to explain the dispute over the Kashmir region in the perspective of international law.  Based on the results of the study, the conflict that occurred between India and Pakistan in the struggle for the Kashmir region under international law is a dispute, because the Kashmir region is equally claimed by India and Pakistan. The dispute over the Kashmir region occurred because of two factors, namely religious factors and border factors.  Because the Indian and Pakistani conflict against the Kashmir region is an international conflict, the resolution of this conflict also involves the involvement of international organizations namely SAARC and the United Nations.  SAARC is an economic and political organization of eight countries in South Asia and is one of the platforms that aims to promote and strengthen collective self-confidence among South Asian countries.  SAARC seeks to be a vehicle for peace in India and Pakistan.  The United Nations was formed with one of its aims to ensure world peace and security.  The two organizations are both looking for solutions to the dispute that occurred in Kashmir.